2022
DOI: 10.3390/atmos13071126
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Effects on Rainfall Partition and Throughfall Drop Size Distribution in a Tropical Dry Forest

Abstract: The energy distribution of natural rainfall droplets at different stages of canopy development in low-latitude semi-arid environments is still understudied. We assessed relationships between canopy development, gross rainfall (P) and throughfall (TF) characteristics in a tropical dry forest (TDF) with a total of 95 events of natural rain during December 2019–July 2021, in Northeast Brazil. One disdrometer was installed in an open field to record the gross rainfall and another under the deciduous vegetation can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The alteration in the chemical composition of rainfall as it passes through the canopy has greatly resulted from various factors, including rainfall characteristics, canopy structure, site conditions, and atmospheric deposition [8][9][19][20]. Rainfall and forest canopy, as matter transport carriers and the main place where rainfall partitioning occurs, respectively, are the two major factors affecting the net rainfall input of base cations in forest ecosystems [20][21][22]. When rainfall is small and evaporation is strong, most of the rainwater was intercepted on canopy without the formation of throughfall and stemflow and transport of base cations.…”
Section: Introductionmentioning
confidence: 99%
“…The alteration in the chemical composition of rainfall as it passes through the canopy has greatly resulted from various factors, including rainfall characteristics, canopy structure, site conditions, and atmospheric deposition [8][9][19][20]. Rainfall and forest canopy, as matter transport carriers and the main place where rainfall partitioning occurs, respectively, are the two major factors affecting the net rainfall input of base cations in forest ecosystems [20][21][22]. When rainfall is small and evaporation is strong, most of the rainwater was intercepted on canopy without the formation of throughfall and stemflow and transport of base cations.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al (2002) similarly demonstrated that following vegetation restoration, there was a notable enhancement in the water stability of soil aggregates. Vegetation mainly affects soil aggregate changes in the water erosion process as follows (Figure 1): (1) Vegetation effectively intercepts rainfall through the aboveground branches and leaves and reduces soil aggregate breakup (Alizadehtazi et al, 2020; Brasil et al, 2022; Gardon et al, 2020); (2) Vegetation increases the surface roughness and slows the surface runoff velocity, thereby weakening the runoff erosion energy and reducing the occurrence of erosion (Du et al, 2019; Liu et al, 2017; Shi et al, 2022), it leads to reduced loss of soil aggregates; (3) Vegetation enhances the stability of the soil aggregate structure through the underground part of the root system and improves the soil erosion resistance (Liu et al, 2022; Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%